Thermodynamic limits of the depolymerization of poly(olefin)s using mechanochemistry - Chang, Yuchen; Nguyen, Van Son; Hergesell, Adrian H; Seitzinger, Claire L; Meisner, Jan; Vollmer, Ina; Schork, F. Joseph; Sievers, Carsten (RSC Mechanochemistry, 2024)
Mechanochemistry is a promising approach for chemical recycling of commodity plastics, and in some cases depolymerization to the monomer(s) has been reported. However, while poly(olefin)s comprise the largest share of global commodity plastics, mechanochemical depolymerization of these polymers in standard laboratory-scale ball mill reactors suffers from slow rates. In this work, the observed reactivities of poly(styrene), poly(ethylene) and poly(propylene) are rationalized on the basis of thermodynamic limitations of their depolymerization by depropagation of free radical intermediates. In addition, subsequent phase partitioning equilibria for the removal of monomers from the reactor via a purge gas stream are discussed for these polymers. For poly(styrene), a typical vibratory ball mill supplies just enough energy for its depolymerization to be driven by either thermal hotspots or adiabatic compression of the impact site, but the same energy supply is far from sufficient for poly(propylene) and poly(ethylene). Meanwhile, removal of styrene from the reactor is thermodynamically hindered by its lower volatility, but this is not an issue for either propylene or ethylene. The implications of these thermodynamic limitations for mechanochemical reactor design and potential for mechanocatalytic processes are highlighted. Feasibility of mechanochemical depolymerization of commodity poly(olefin)s in a ball mill reactor is assessed using thermodynamic data.